PENINGKATAN NILAI KUAT TEKAN DAN PERBAIKAN RETAK-RETAK PADA BETON DENGAN MENGGUNAKAN FIBER KAWAT BENDRAT BENTUK “Z” DENGAN 3 (TIGA) VARIASI CAMPURAN: Indonesia - Juanita Juanita (Universitas Majalengka, 2021)
Concrete is the main basic material used for the planning and design of widely used structures. This is because concrete has a very high compressive strength value when compared to other materials. However, concrete also has weaknesses, one of which is its brittle nature. Therefore, in this study, the use of Z-shaped bendrat wire will be carried out to increase the value of the compressive strength of concrete while improving the brittle nature of the concrete.In this study, bendrat wire fiber in the form of Z was used with a mixed variation of 0.5%, 0.75% and 1%. The number of test objects made is 12 pieces. The test was carried out when the specimen was 28 days old by using a Compression Testing Machine (CTM). From the results of the study, the average compressive strength value for normal concrete (SN) was 26.46 MPa, for Z-shaped bendrat wire fiber concrete with a mixed variation of 0.5% (SF1) the average compressive strength value was 27.27 MPa, for fiber concrete bendrat wire Z shape with a mixed variation of 0.75% (SF2) the average compressive strength value is 28.03 MPa, and for fiber concrete wire bendrat Z shape with a mixed variation of 1% (SF3) the average compressive strength value is 28.21 MPa. The more Z-shaped bendrat wire fibers added to the concrete mix, the higher the compressive strength value and the smaller the cracks that occur in the concrete.